THE EFFECTIVENESS OF VIRTUAL REALITY IN REDUCING ANXIETY IN HEMODIALYSIS PATIENTS: NARRATIVE REVIEW - Mesya Mesya; Reni Muhka (CV. Adiba Aisha Amira, 2025)
Chronic Kidney Disease (CKD) requires regular hemodialysis therapy to replace impaired kidney function. However, this procedure often causes anxiety that impacts psychological well-being and patient compliance with treatment. One of the developing non- pharmacological interventions is Virtual Reality (VR), which is used as a distraction technique to reduce anxiety during hemodialysis. This review aims to evaluate the effectiveness of using VR in reducing anxiety in patients undergoing hemodialysis therapy. This study is a systematic review with a literature search from the Google Scholar, ProQuest, and PubMed databases for the period 2020–2025. The keywords